CGIAR Genetic Innovation Action Area: Theory of Change and Results Framework - Bonaiuti, Enrico; Vermeulen, Sonja; Belcher, Brian; Philip Craven Thiele, Graham; Hunt, Adam Christopher; Barker, Ian; Derera, John; Lusty, Charlotte; Syed Alwee, Sharifah Shahrul (CGIAR System Organization, 2023)
The theory of change depends on all work being done within partnerships, particularly with national research and extension systems(NARES) and with small and medium enterprises (SMEs) active in the national breeding and seed sectors. A core focus is to raise the NARES-CGIAR-SME breeding networks’ collective strategic and operational capacity to deliver a high rate of uptake and replacement in seed varieties among small-scale farmers in low- and medium- income countries. Co-generated genetic innovations will be delivered as part of integrated solutions across CGIAR. Together with System Transformation and Resilient Agrifood Systems Action Areas for food, land and water systems, and through close cooperation with CGIAR’s strategic partners, Genetic Innovation will enable progress on nationally defined pathways for development. Major effort will go into achieving affordable, accessible and fair benefits to low-income farmers, with particular emphasis on ensuring that research outcomes lead to greater equality for women. Genetic Innovation will contribute across all five of CGIAR’s Impact Areas, through maintenance of agrobiodiversity and through accelerated adoption by farmers of demand-driven improved crop varieties, delivered as part of integrated bundles of institutional and technical innovations that are designed to respond to priorities in partner countries.